Analisis Bahasa Anak pada Usia 2 Tahun dari Aspek Fonologi, Morfologi, Sintaksis, dan Semantik - Zira Fatmaira (Medan Resource Center, 2022)
Mother tongue is the first language mastered by humans since the beginning of their life through interaction with fellow members of the language community, such as family and the environmental community. This shows that the first language is an initial process obtained by children in recognizing sounds and symbols called language. The process of language acquisition also develops with increasing age of children, from months of age to years of age, but what is discussed in this study is the age of 2 years 6 months in which the language process has begun to be clearly seen in the vocabulary spoken by the child. This study aims to determine the language acquisition of children aged 2 years 6 months at the level of phonology, morphology, syntax and semantics. This research is expected to be one of the information materials in terms of research on language acquisition. The research method used in this research is a qualitative method with a case study approach. Through this qualitative method, the fathian phonetic system will be described at the age of 2 years and 6 months.